Wordsearches Widen Your Vocabulary in English - Wallwork, Adrian (Easy English!, 2018)
On the train, on the beach, on the sofa ... many people in all parts of the world enjoy doing wordsearches. If you are studying English and want to learn and practise vocabulary related to various topics, then this book is for you! The topics reflect the kinds of everyday conversations that you might have both with native and non-native speakers of English. The topics are also those that are typically tested in English examinations e.g.TOEFL, Cambridge (First Certificate, Advanced), IELTS, and Trinity. Each chapter begins with a list of questions to enable you to have a conversation about a particular topic in various situations: on a social occasion (e.g. a work dinner, a conference lunch, a party); in the classroom during an English lesson; when chatting, either face to face or online; and during an English oral exam. After the list of questions, you will find a Word List associated with the topic and exercises to test your knowledge of less common words. The final aim is then to find the words from the Word List in the related Wordsearch. Easy English! is a series of books to help you learn and revise your English with minimal effort. You can improve your English by: reading texts in English that you might normally read in your own language e.g. jokes, personality tests, lateral thinking games, and wordsearches; doing short exercises to improve specific areas grammar and vocabulary, i.e. the areas that tend to lead to the most mistakes - the aim is just to focus on what you really need rather than overwhelming yourself with a mass of rules, many of which may have no practical daily value. Other books in the Easy English!series include: Wordsearches: Widen Your Vocabulary in English Test Your Personality: Have Fun and Learn Useful Phrases Word games, Riddles and Logic Tests: Tax Your Brain and Boost Your English Top 50 Grammar Mistakes: How to Avoid Them Top 50 Vocabulary Mistakes: How to Avoid Them.